Subacute Toxicity Test of (Scaevola taccada Gaertn.) Roxb Leaf Extract on Kidney and Liver Function in Rats (Rattus norvegicus) - Tenri Ayu Adri; Aritzah Dwi Widati; Peter Kabo; Yulia Yusrini Djabir (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2021)
Beruwas laut leaf (Scaevola taccada (Gaertn.) Roxb has pharmacological effects such as anti-inflammatory, analgesic, antioxidant, antidiabetic and anticancer. Although beruwas laut leaf have many advantages, safety is the main requirement that herbal medicine must have. This research was aimed to prove sebacute of beruwas laut leaf (Scaevola taccada (Gaertn.) Roxb.) about the function of kidney and liver. This research used 20 rats were devided into 4 groups. Group 1 as a control group and groups 2,3, and 4 as an experimental group by administration of beruwas laut leaf extract with dose 200 mg/kgBB, 400 mg/kgBB, and 600 mg/kgBB. The extract was made using maceration and sebacute toxicity testing was carried out for 14 days. After giving the extract, some of rats had diarrhea. The results showed significant effect to increase levels of ureum and CGT after administration of dose 400mg/kgBB. Moreover, administration of dose 600 mg/kgBB caused significant effect in liver biomarkers and kidney (GGT and ureum). It was concluded that ethanol extract of beruwas laut leaf (Scaevola taccada (Gaertn.) Roxb.) with dose 200mg/kgBB showed safe but toxic to kidney and liver with dose 600mg/kgBB.